Development and characterization of blue ternate (Citoria ternatea L.) pandesal using various coconut (Cocoos nucifera L.) flour formulations. - Mayordomo, Aika Marquillero
Blue ternate pandesal product was developed using various coconut flour formations, the formulations were prepared by blending coconut flour to wheat flour in ratios of F1(0:100), F2(10:90), F3(20:80) and F4(30:70). Physico-chemical, proximate, and organoleptic properties of the product were evaluated to determine if coconut flour formulations affected specific parameters being analyzed. Using texture profile analysis parameter, only bread hardness with 0.87 to 3.76N exhibited a significant difference between formulations. Water activity (aw) obtained 0.9413 to 0.9467 exhibited to have a significant difference (p≤0.05) among formulations. moisture content of the product resulted from 34.85% to 38.54% which displayed the highest proportion of the proximate composition of the product, crude ash obtained were 3.06 to 3.21% crude protein resulted from 10.65 to 11.14% and crude fiber obtained 2.88 to 11.60%. The proximate analyses showed a significant difference (p≤0.05) among the formulations except for crude fat, which resulted from 16.21 to 20.21%. The sensory evaluation was performed with 15 well-oriented panelists using a descriptive test which determined the blue ternate color distribution for the appearance of the product, coconut-like odor, coconut-like flavor, texture, and taste. The F2 was ranked by the panelist as the most preferred formulation using rank sum preference test. The F2 product was subjected to consumer acceptability using a 9-point hedonic scale with 100 respondents randomly chosen for a specific company. Fourty-four percent of the respondents rated the product as "like very much" while 36% moderately liked the product. Furthermore, the raw material cost per piece of the control (F1) is ₱2.75, and the most preferred formulation (F2) is ₱2.82.